The relationships between use of alcohol, tobacco and coffee in adolescence and mood disorders in adulthood - Bolstad, Ingeborg; Alakokkare, Anni Emilia; Bramness, Jørgen G.; Rognli, Eline B.; Levola, Jonna; Mustonen, Antti; Miettunen, Jouko; Niemelä, Solja (Acta Psychiatrica Scandinavica, 2022)
Introduction: Alcohol, tobacco and coffee are commonly used substances and use in adolescence has previously been linked to mood disorders. However, few large prospective studies have investigated adolescent use in relation to mental health outcomes in adulthood. The main aim of this study was to examine the prospective associations between alcohol use, cigarette smoking and coffee consumption at age 16 and subsequent mood disorders up to 33 years of age. Methods: Data from The Northern Finland Birth Cohort 1986 Study were used and a total of 7660 participants (49.9% male) were included. Associations between alcohol use, cigarette smoking and coffee consumption at age 16 and later diagnoses of major depression and bipolar disorder were examined using multinomial logistic regression analyses. Results: Mean number of cigarettes/day (OR, 1.23 [95% CI 1.01–1.50]) and mean volume of alcohol consumption (OR, 1.22 [95% CI 1.01–1.47]), but not frequency of excessive drinking, in adolescence were associated with increased risk for subsequent bipolar disorder after adjustment for sex, parental psychiatric disorders, family structure, illicit substance use, and emotional and behavioral problems at age 16. An association between cigarette smoking and major depression attenuated to statistically non-significant when adjusted for emotional and behavioral problems. No associations were observed between adolescent coffee consumption and subsequent mood disorders. Conclusions: This is the first study to report an association of adolescent cigarette smoking and subsequent bipolar disorder diagnosis providing grounds for further research and pointing to a place for preventive measures among adolescents. Peer reviewed